DISCUSSION ON THE TEACHING OF CALCULATION METHOD - Li, Aijuan (IJRDO -JOURNAL OF MATHEMATICS, 2022)
According to the problems in the teaching of calculation method, we give some methods. We can make full use of mobile phones for testing. Moreover,  teaching can get feedback from scientific research. Furthermore, we can use resources after class. Based on the above methods, we can improve students' enthusiasm and participation in learning this course.